Traumatic Distal Ulnar Artery Thrombosis - Ahmet A. Karaarslan; Ahmet Karakaşlı; Aslan Mayda; Tolga Karcı; Hakan Aycan; Şenol Kobak (Case Reports in Orthopedics)
This paper is about a posttraumatic distal ulnar artery thrombosis case that has occurred after a single blunt trauma. The ulnar artery thrombosis because of chronic trauma is a frequent condition (hypothenar hammer syndrome) but an ulnar artery thrombosis because of a single direct blunt trauma is rare. Our patient who has been affected by a single blunt trauma to his hand and developed ulnar artery thrombosis has been treated by resection of the thrombosed ulnar artery segment. This report shows that a single blunt trauma can cause distal ulnar artery thrombosis in the hand and it can be treated merely by thrombosed segment resection in suitable cases.